La niña de tus ojos (1998) a la luz de Carmen la de Triana (1938): parodia y subversión de la identidad española. - Moreno-Díaz, Carmen (Hispanic Research Journal, 2015)
Spanish identity is one of the main themes that articulate the film directed by Fernando Trueba, La niña de tus ojos (1998). This is made evident by the presence of a parodic intent that runs through scenes that recreate the shooting of an españolada, a movie with an exaggeratedly Spanish 'flavor' originating in the early 1930s. With this meta-cinematographic technique, the artificiality and the reconstruction of a national stereotype are emphasized. The present article analyses how such an undermining and parody affect the topic of Spanish identity in La niña de tus ojos. In order to do so, I will consider, first, the cinematographic category of españolada as a model that Trueba adopts in order to parody it through meta-cinematographic scenes that emphasize its artificiality. The comparison with the film Carmen la de Triana (1938) by Florián Rey, evocated in La niña de tus ojos, will be crucial to illustrate concrete examples of parody. Secondly, I shall analyse examples of the recreation of the Andalusian landscape, and the traditional figures such as gypsies and bandoleros. Finally, I shall explore how the folk singer, Macarena Granada, performs shows whose lack of orthodox conventionality contrasts radically with the normative españolada of the 1930s in general, and with Carmen la de Triana in particular.